Achieving parallelly-arranged Ti3C2Tx in epoxy coating for anti-corrosive/wear high-efficiency protection. (15th February 2022) - Fan, Xiaoqiang; Yan, Han; Cai, Meng; Song, Shijie; Huang, Yu; Zhu, Minhao
Abstract: Two-dimensional Ti3 C2 Tx has demonstrated great potential for enhancing the protection performance of epoxy coating, but randomly-arranged Ti3 C2 Tx fails to meet higher expectations on the anti-corrosion/wear under extreme conditions. Here, the positively-charged Ti3 C2 Tx (f + -Ti3 C2 Tx ) flakes obtained by functionalization and protonation were directionally distributed in the epoxy coating using an electrophoretic deposition method. The migration/rotation of f + -Ti3 C2 Tx flakes under electric field force and their mutual repulsion are responsible for the parallel alignment with the horizontal direction of coating. In particular, the epoxy coating incorporated with 1 wt % f + -Ti3 C2 Tx exhibits a near-perfect internal arrangement structure. When exposed to saline solution for the long period, its water absorption is decreased by 85.33% and the lowest-frequency impedance is increased by four orders of magnitude compared with randomly-arranged Ti3 C2 Tx hybrid epoxy coating, because parallelly-arranged f + -Ti3 C2 Tx with orientation factor can maximize the internal tortuosity and optimize the barrier properties of epoxy coating against aggressive ions. Furthermore, a significant friction reduction and an order of magnitude reduction in wear rate are obtained, mainly based on the increase of the deflection and branching of cracks in the friction process thus decreasing the probability of coating exfoliation. Therefore, the directional alignment of Ti3 C2 Tx in the epoxy coating can immediately upraise the protection properties' ceiling, specifically suitable for long-term anti-corrosion/wear applications. Graphical abstract: Image 1 Highlights: The positively charged f + -Ti3 C2 Tx is successfully arranged in parallel by electric field action. The physical barrier network with the largest tortuosity formed by the parallelly-arranged f + -Ti3 C2 Tx array significantly inhibits the penetration rate of corrosive ions. The horizontal regular arrangement of f + -Ti3 C2 Tx increases deflection and branching of cracks during defect growth, and thus reducing coating exfoliation. This work raises the anti-corrosion/wear ceiling of Ti3 C2 Tx -based epoxy coatings, and the facile preparation process is conducive to large-scale practical applications.